Pengaruh Layanan Dan Informasi Online Terhadap Keputusan Penggunaan Jasa Aplikasi Grab Dengan Word Of Mouth Sebagai Variabel Intervening (Studi Kasus Mahasiswa Manajemen Universitas Muhammadiyah Metro) - Desy Fitria Ramadhani; Ratmono; Selamet Fuadi (Universitas Muhammadiyah Metro, 2025)
This research used descriptive quantitative approach which the aims to determine thesignificance of online services and information on the decision to use Grab applicationservices with Word Of Mouth as the intervening variable with a case study ofMuhammadiyah Metro University management students batch 19. The sample in thisresearch used 103 management students. The results of the analysis show that service qualityhas a significant effect on the decision to use grab application services with, onlineinformation has a significant effect on the decision to use grab application services and theword of mouth variable is an intervening variable that has a significant effect andstrengthens the relationship between online services and information and the decision to useservices